Estimating the natural rate of unemployment for Ukraine - Artem Vdovychenko (Graduate Institute of International and Development Studies, 2022)
In this study, we apply the Kalman filter to estimate the set of reduced-form Phillips curves for different types of inflation in Ukraine. Based on the estimated models, we derive a number of series of non-accelerating inflation rate of unemployment (NAIRU) that provide information about the general trajectory and last tendencies of trend unemployment. To better identify the unemployment trend, we include indicators of long-term unemployment and the Beveridge curve shifts as exogenous variables in the NAIRU equation. Both variables demonstrate a significant impact on NAIRU dynamics. Our estimates show that the Phillips curve slope in Ukraine lies in a standard range of -0.3 to -0.5, with high statistical significance. The median value of estimated NAIRUs was at its lowest at 7.2% at the end of 2008, after which it gradually increased to 9.4% by the end of 2021.
Keywords: E24; E31; 330; Phillips curve; unemployment; NAIRU; Kalman filter; Beveridge curve